Penerapan Alat Bukti Persangkaan dalam Putusan Cerai Gugat di Pengadilan Agama Padang Kelas IA - mulyanto mulyanto (CV Rewang Rencang, 2025)
This study aims to analyze the application of presumptive evidence in divorce rulings at the Religious Court of Padang Class IA. Presumptive evidence is used to strengthen other evidence in the resolution of divorce cases. Although most of the witnesses presented do not meet the qualifications as valid evidence, presumption is still accepted by judges as valid and legitimate evidence, not replacing other evidence but rather reinforcing it in the process of proving the case. This research also examines the role of presumptive evidence in assisting judges in formulating fair decisions, especially in situations where direct evidence is limited. The findings indicate that presumption plays a significant role in helping judges reach fair decisions by considering the available evidence. In conclusion, the application of presumption is crucial in the evidence system at the Religious Court of Padang, particularly in divorce cases, as it assists judges in reaching objective and just conclusions.